Assessment of the clogging potential of two clays - Kang, Chao (2020)
Clogging sometimes occurs in tunnelling projects. Soils containing high plasticity clay minerals have a high potential for clogging. To gain a better understanding of the effect of swelling clay on the clogging potential, two different clays, bentonite and kaolin, were tested in different proportions. Several approaches were employed to evaluate clogging potential, including a semi-empirical diagram, laboratory-based drilling tests, and evaluation of the variation of the plasticity indexes. The performance of an additive was also evaluated using the same method as for pure mixtures. To determine the correlation between the mechanical properties and clogging potential of the mixtures, vane shear tests were carried out on the mixtures containing the additive. The results revealed that mixtures with bentonite had a higher clogging potential than pure kaolin. The performance of additives used for mitigation of clogging also changed with the content of bentonite in the mixtures. The simple drilling tests were capable of quantitatively differentiating the clogging potential of plain mixtures and evaluating the performance of additives.